Integrating Narrative Characters in Early Childhood Music Learning: A Study of Mozart Mouse and Beethoven Bear Impact on Early Learners - Dihita Sagala, Mastri; Widyatama Putra, Zakarias Aria (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This research explores the implementation of Mozart Mouse and Beethoven Bear characterization methods in the Little Musician class at Favore Music School, Bandung. It assesses their impact on young learners' musical, linguistic, and emotional development. Utilizing a qualitative approach, the study spanned six months and incorporated observations, interviews, and document reviews to gather comprehensive data. The Music for Little Mozarts curriculum, designed specifically for young children, integrates narrative characters to enhance student engagement and learning. Data analysis followed the Miles and Huberman model, focusing on data reduction, display, and conclusion to ensure robust, systematically derived findings. Results indicate that preparing and implementing character-based materials and musical instruments effectively engages children. The role-playing exercises using Mozart Mouse and Beethoven Bear deepened the children's understanding of musical concepts, such as pitch and dynamics, and significantly improved their emotional and linguistic skills. This was particularly evident in their enthusiastic participation in end-of-semester musical concerts. The study highlights the potential of incorporating narrative and creativity in early education to enrich learning outcomes. Character-based methods could be particularly beneficial for fostering comprehensive developmental skills in music education. However, the research was limited to a single educational setting and a short observation period, which might affect the generalizability of the results. Future research should expand the study to multiple settings and extend the observation period better to understand the long-term effects of such pedagogical strategies. This could help ascertain the effectiveness and adaptability of characterization methods in a broader educational context.